2022
DOI: 10.3991/ijim.v16i06.28905
|View full text |Cite
|
Sign up to set email alerts
|

Examining Teachers’ Intention to integrate Robotics-based Storytelling Activities in Primary Schools

Abstract: Though expanding computational thinking to primary school students has become more prevalent, there is a lack of appropriate didactics. Educational robotics offers a possible approach. However, innovations can only find their way into the classroom if teachers find them feasible and meaningful. Thus, appropriate training and further education of teachers are becoming a necessity. This paper reports on investigating professional development for teachers in programming robots by integrating the method of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…It is important to point out the benefits associated with using virtual robotics in a webmediated learning process that is cited by the participants, including: achieving the desired outcomes related to STEM skills and knowledge; mobility and fixability; more student accessibility; lower costs; reinforcing knowledge through trial and error with no consequences; critical thinking; promoting interpersonal skills; improving team work; and improving problem solving and reasoning skills. These outcomes are also associated with learning with physical robotics, as established by many studies ( Witherspoon et al, 2016;Anwar et al, 2019;González-García et al, 2020;Lamb et al, 2020;Wright et al, 2021;Mistretta, 2022;Tengler and Sabitzer, 2022). The main barriers that were noted were associated with web-mediated cultural norms, lack of interest, and regulations/policies promoting positive practices related to virtual learning with robotics.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It is important to point out the benefits associated with using virtual robotics in a webmediated learning process that is cited by the participants, including: achieving the desired outcomes related to STEM skills and knowledge; mobility and fixability; more student accessibility; lower costs; reinforcing knowledge through trial and error with no consequences; critical thinking; promoting interpersonal skills; improving team work; and improving problem solving and reasoning skills. These outcomes are also associated with learning with physical robotics, as established by many studies ( Witherspoon et al, 2016;Anwar et al, 2019;González-García et al, 2020;Lamb et al, 2020;Wright et al, 2021;Mistretta, 2022;Tengler and Sabitzer, 2022). The main barriers that were noted were associated with web-mediated cultural norms, lack of interest, and regulations/policies promoting positive practices related to virtual learning with robotics.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, many studies have indicated that teaching STEM with robotics might be a successful solution for achieving outcomes that are difficult to achieve through conventional classroom methods (Kopcha et al, 2017;Angeli and Valanides, 2019;Shan et al, 2019). Additionally, cost, flexibility, mobility (Alsoliman, 2018;Hammack and Ivey, 2019;Tengler and Sabitzer, 2022), and, more recently, unpredictable global circumstances such as the COVID-19 pandemic, are factors that should be considered when deciding on which STEM teaching methods, facilitated by robotics, should be implemented. Studies have highlighted that virtual robotics can compensate for the lack of physical presence by offering features like mobility, flexibility, and accessibility to all students (Gucwa and Cheng, 2017;Lamb et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The teachers can be in service or students preparing to be teachers (Esteve-Mon et al, 2019;Angeli, 2022), mainly in primary school (one case also in kindergarten). The number of subjects involved in the studies varies from 4 and 350, just like the kind of research that can be organized as experimental or quasi-experimental with pre-post tests on computational thinking, digital competencies, algorithmic thinking, and debugging skills (IN-COTIC and CT test in Esteve-Mon et al, 2019, Technology Usage Inventory, TUI in Tengler and Sabitzer, 2022) or according to qualitative or mixed approaches. For example, the study of Chalmers (2018), one of the three most cited among those selected in the review, is structured as multiple case studies on four teachers in Australia whose goal is to examine the perceptions of teachers in the implementation of WeDo 2.0 robot kits in their classrooms.…”
Section: Robot Teaching and Computational Thinkingmentioning
confidence: 99%
“…The methods are related to using robotics to work on CT; the only interdisciplinary method to teach robotics together with storytelling is Tell, Draw, and Code (Tengler and Sabitzer, 2022). In the papers, together with unplugged activities, we find the use of robots such as Bee-bots, ozobot, mBots, software such as Scratch, and systems such as Makey-Makey and Arduino.…”
Section: Robot Teaching and Computational Thinkingmentioning
confidence: 99%
“…As educators prepare students for college and career readiness, computational thinking skills, including coding and robotics, are being taught in the K12 educational environment. Educational robotics offers a possible approach to introduce computer science education at the primary level as a didactic tool to promote computational thinking (Tengler & Sabitzer, 2022).…”
Section: Introductionmentioning
confidence: 99%